Notoginsenoside R1, a metabolite from Panax notoginseng (Burkill) F.H.Chen, stimulates insulin secretion through activation of phosphatidylinositol 3-kinase (PI3K)/Akt pathway - Al-Romaiyan, Altaf; Barakat, Ahmad; Marafie, Sulaiman K.; Masocha, Willias (Frontiers in Pharmacology, 2024)
Background: For ages, botanical medicine has been used in the treatment of diabetes mellitus (DM). Notoginsenoside R1 (NGR1), a Panax notoginseng (Burkill) F.H.Chen metabolite, has been documented to possess antidiabetic action in vivo. However, its precise molecular mechanism of action is not clear.We evaluated NGR1's effects on blood glucose in vivo and then evaluated in vitro whether NGR1 has effects on insulin secretion and the probable molecular pathways involved in NGR1-induced insulin secretion.Methods: Diabetes was induced in mice by streptozotocin (STZ). Glucose tolerance test was performed before and after NGR1 was administered intraperitoneally to diabetic animals for 4 weeks. Static and perifusion experiments were performed using isolated female BALB/c mouse islets. Preproinsulin (Ins) mRNA expression was measured using q-PCR. Protein expression of PI3K/Akt pathway was assessed using the fully automated Wes TM capillary-based protein electrophoresis.Results: Treatment of diabetic mice with NGR1 improved their glucose intolerance. In vitro, NGR1 increased insulin secretion in a concentration-dependent manner. NGR1 initiated the secretion of insulin at 2 mM glucose and augmented glucose-stimulated insulin secretion which was sustained throughout NGR1 perifusion. NGR1-induced insulin secretion was not altered by a voltage gated calcium channel blocker or protein kinase A inhibitor. NGR1 did not significantly modulate Ins mRNA expression. However, NGR1 significantly increased the levels of phospho-Akt and phopho-p-85. In conclusion, this study has shown that NGR1 ameliorates hyperglycemia in diabetic mice. NGR1 has a direct insulin secretagogue activity on mouse islets, stimulates insulin secretion at both basal and postprandial glucose concentrations, and activates PI3K/Akt pathway to induce insulin secretion. These results suggest that NGR1 may provide an alternative therapy to manage DM.